Short Note: A Remark on "An Efficient Real Space Method for Orbital-Free Density-Functional Theory" (Communications in Computational Physics, 2008)
In this short note we clarify some issues regarding the existence of minimizers for the Thomas-Fermi-von Weiszacker energy functional in orbital-free density functional theory, when the Wang-Teter corrections are included.